Increase in Neutrophil Lymphocyte Ratio in COVID-19 Patients Based on Symptom Severity - Prasetya, Hieronymus Rayi; Muhajir, Nurlaili Farida; Wati, Mey Rena; Murtiningrum, Sri (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2024)
The neutrophil lymphocyte ratio (NLR) is an indicator of the presence of a systemic inflammatory response. The neutrophil lymphocyte ratio parameter was calculated by comparing the number of neutrophils and the number of lymphocytes. Patients with severe COVID-19 who did not survive were found to have a higher neutrophil lymphocyte ratio compared to patients with a mild prognosis. Thisstudy uses a descriptive method, which aims to describe the value of the neutrophil lymphocyte ratio in COVID-19 patients based on the severity of symptoms. The average value of high neutrophil lymphocyte ratio (NLR) in COVID-19 patients occurred in the severe (6.12%) and critical (10.78%) categories. The average value of high neutrophils (Neutrophilia) in COVID-19 patients occurred in the severe (76%) and critical (82%) categories. The average value of low lymphocytes (lymphocytopenia) in COVID-19 patients occurred in the severe 17% and critical 12% category. The NLR value in patients with the severe category had an increase in the NLR value twice thenormal value, while in the critical category had an increase in the NLR value three times the normal value.